T.g.v. de 90ste verjaardag van Jan van Zutphen. 3de van links Mug naast Van Zutphen en zijn vrouw (1953)
T.g.v. de 90ste verjaardag van Jan van Zutphen. 3de van links Mug naast Van Zutphen en zijn vrouw.